Karakteristik Komposit Bioplastik Maizena dan Glukomanan pada Perlakuan Jenis dan Konsentrasi Bahan Pengisi - Aini, Anissa Fitri Nur; Hasojuwono, Bambang Admadi; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): Desember, 2021)
This study aims to know the effect of the type and concentration of filler on the characteristics of cornstarch and glucomannan bioplastic composites, and determine the type and concentration of fillers that can produce bioplastic composites that meet the Indonesian National Standard (SNI) and International Standard. This study used a randomized block design with two factors. Factor I is a type of filler consisting of ZnO, CaCO 3 , clay, nanocellulose. Factor II is the concentration of filler which consists of 4 levels, namely 0%; 5%; 10%; 15%. This experiment resulted in 16 treatment combinations and were grouped into 2 groups so that 32 experimental units were obtained. The data were analyzed for diversity and continued with the Tukey test using Minitab17 software. The results showed that the type and concentration of filler had a very significant effect on tensile strength, elongation, modulus young, swelling, biodegradation and had a significant effect on WVTR. The interaction has a very significant effect on tensile strength, modulus young, swelling, WVTR and has a significant effect on elongation and biodegradation. Cornstarch and glucomannan bioplastic composites that meet the Indonesian National Standard (SNI) and International Standard on tensile strength and biodegradation variables using nanocellulose fillers with concentrations of 10% and 15% which have tensile strength characteristics of 15,23 and 16,93 MPa, elongation at break of 11,47 and 10,76 %, modulus young of 132,81 and 158,61 MPa, swelling of 68,93 and 69,58 %, WVTR 1,18 and 1,24 g/m 2 .hr, biodegradation rate for a long time 7 days. Maizene and glucomannan bioplastic composites contain hydrocarbon functional groups -(CH 2 )n, carboxyl (C-O), alkene (C=C), alkyne (C?C), hydroxyl carboxylic acid (O-H), hydroxyl alcohol (O-H), carbonyl (C=O) and aromatic compounds (C-H). Keywords: bioplastic composite, cornstarch, glucomannan, ZnO, CaCO 3 , clay, nanocellulose